If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 50 = 6x + 50 Reorder the terms: 50 + 4x = 6x + 50 Reorder the terms: 50 + 4x = 50 + 6x Add '-50' to each side of the equation. 50 + -50 + 4x = 50 + -50 + 6x Combine like terms: 50 + -50 = 0 0 + 4x = 50 + -50 + 6x 4x = 50 + -50 + 6x Combine like terms: 50 + -50 = 0 4x = 0 + 6x 4x = 6x Solving 4x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4x + -6x = 6x + -6x Combine like terms: 4x + -6x = -2x -2x = 6x + -6x Combine like terms: 6x + -6x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 1/3(3.14×9)9 | | -3x+5=x-13 | | X-1+5x=2x | | X(x+4)=525 | | 56-n=48 | | 0.30(d-1000000)=202500 | | 11x^2-8=2x | | 4i*i= | | Tan(64)=7/x | | 3+(x-2)=8 | | 10*190+6.25*177.8+5= | | 13x-16x+18x=60-26x+11x | | 2x^3-10x^2+40x=8x | | x^5+9=26 | | 2x^2-10x+40x=8x | | 2-2x=-5-x | | 3x^2-x=140 | | log(x+3)=log(x-3)+1.5 | | 3x^2+4-7x=0 | | B+63=19 | | -4=p+12 | | ln(x+3)=ln(x-3)+1.5 | | 4tanx=10 | | 8b+3=b | | 16+11h=9h | | 8x+26=4x+2 | | 7y-8=4y+31 | | (7x-68)=(-3+110) | | 6x+26=8x+12 | | 3y+-1=7 | | (3x-10)=(3x-2) | | 3x^2+y^2=4 |